Javanese Women’s Reprenstation in Adaninggar – Kelaswara Dance - Prihatini, Luciana Intan; Iswidayati, Sri; Hartono, Hartono (Catharsis, 2018)
Adaninggarelaswara dance is a classical dance which got influence of Chinese ethnic. The dancers’ movements called gesture meaningful with normative value of Javanese woman as well as still relevant in Javanese woman lives today. The research aims to describe Adaninggar-Kelaswara dance performance, identify women’s representation in Adaninggar-Kelaswara dance movement and also to communicate the pragmatic message to women through Adaninggar-Kelaswara dance movement. The method of this study used qualitative method and interpretative semiotics approach. The source of data used primary and secunder data through the techniques of data were observation, interview, and documentary. The technique of authorized data was the use of source triangulation and the techniques of analyzing data using Barthes cultural semiotic. The conclusion of the dance movement in cultural semiotics indicate that Adaninggar-Kelaswara dance movement relating to the way of live and Javanese woman’s personality values. This finding is hoped to become the referential for the further research on Adaninggar-Kelaswara dance with other methods in order to explore the cultural values of Java, especially concerning to women representation.